Hybrid activist collectives: reframing mothers' environmental and caring labour. Issue 9 (12th September 2016) - Dombroski, Kelly
Abstract : Purpose: The purpose of this paper is to use a case study of an online parenting forum to theorise how mothers' everyday environmental and caring labour is a form of environmental and social activism in the home, that while not organised as such, is still collectivised in a "hybrid activist collective". Design/methodology/approach: Using ethnographic data and content analysis from an online parenting forum for the nappy-free infant hygiene practice known as "elimination communication", the author compares the matters of key concern arising for this group of mothers with economic activist concerns as identified by Gibson-Graham et al. (2013) in their community economies work. Findings: The paper finds a high degree of resonance between the key concerns of the elimination communication forum members with the key concerns of community economies. Furthermore, the author identifies the components of what might comprise a "hybrid activist collective" of mothers and others undertaking direct action for environmental and social change. Social implications: Mothers and others acting for social and environmental change through domestic practices should be recognised for their important environmental and caring labour. Originality/value: The paper proposes the "hybrid activist collective" as a way of understanding the human and non-human elements that gather together to act for environmental and social change in a collectivised, but not formally organised manner.